2018
DOI: 10.1369/0022155418765164
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin Deficiency Is Associated With Expansion of Islet β-Cell Mass in High Fat-Fed Mice

Abstract: Neprilysin (NEP) is an endopeptidase known to modulate nervous, cardiovascular, and immune systems via inactivation of regulatory peptides. In addition, it may also contribute to impaired glucose homeostasis as observed in type 2 diabetes (T2D). Specifically, we and others have shown that NEP is upregulated under conditions associated with T2D, whereas NEP deficiency and/or inhibition improves glucose homeostasis via enhanced glucose tolerance, insulin sensitivity, and pancreatic β-cell function. Whether incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…This effect of green tea was not observed in obese NEP-knockout mice. NEP deficient mice are also characterised by increased islet β-cell mass when fed on a high fat diet which suggests a role for NEP in modulating metabolism of this type of cells ( Parilla et al, 2018 ). Elevated NEP activity was also observed in the vitreous of patients with diabetic retinopathy which inversely correlated with Aβ levels ( Hara et al, 2006 ).…”
Section: Role Of Nep In Diseasesmentioning
confidence: 99%
“…This effect of green tea was not observed in obese NEP-knockout mice. NEP deficient mice are also characterised by increased islet β-cell mass when fed on a high fat diet which suggests a role for NEP in modulating metabolism of this type of cells ( Parilla et al, 2018 ). Elevated NEP activity was also observed in the vitreous of patients with diabetic retinopathy which inversely correlated with Aβ levels ( Hara et al, 2006 ).…”
Section: Role Of Nep In Diseasesmentioning
confidence: 99%
“…Also, islets from neprilysin-deficient mice were protected against palmitate-induced insulin secretory dysfunction in vitro [24]. In vivo, we have shown that high-fat-fed neprilysin-deficient mice display improvements in insulin sensitivity, beta cell function and glucose tolerance, as well as beta cell mass expansion [12,25]. Furthermore, acute inhibition of neprilysin with subcutaneous or intravenous administration of a pharmacological inhibitor increased insulin secretion and sensitivity in a time-and/or dose-dependent manner in pigs, as well as in lean or obese insulin-resistant rats [3,[18][19][20] (Table 1).…”
Section: Evidence For a Beneficial Effect Of Neprilysin Inhibition Onmentioning
confidence: 94%
“…All data presented herein were obtained from refs. [44,54,55,70,72,74,75,78,88,95,96,98,102–111,116,119–121,124–130,132,134–137,140–144,147–156,158,159,161,163–171,173–176...…”
Section: Diet Composition and Exposure Timementioning
confidence: 99%